1982
DOI: 10.1677/joe.0.0920389
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Effect of Oestrogen on Luteinizing Hormone Secretion by the Rat Pituitary Gland

Abstract: Ovariectomized rats with neural deafferentation at the level of the posterior border of the anterior hypothalamic area (AC rats) were used to re-evaluate the direct feedback effect of oestrogen on the regulation of LH secretion by the pituitary gland. Synthetic LH releasing hormone (LH-RH; 300 ng/kg), injected at 30 min intervals into AC rats with undetectable basal LH, induced pulsatile increase of serum LH concentrations. Oestradiol-7Beta (5 micrograms), administered i.v. just before the first LH-RH injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Since we used intact rats in this experiment, it is possible that increased sex steroid hormone concentrations, especially oestrogen, induced by increased serum LH levels, sensitized the pituitary gland to succeeding LH-RH doses. This possibility, however, seems unlikely because our results were in general agreement with in-vitro results obtained using a pituitary perifusion technique by Waring & Turgeon (1980), and oestrogen is known to inhibit LH responsiveness at the pituitary gland to LH-RH a few hours after injection (Libertun et al 1974;Higuchi & Kawakami, 1982). Response of LH to repeated injections of LH releasing hormone (LH-RH; 300ng/kg body wt; shown by arrows) at 30-min intervals in rats ovariectomized for 120 days.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Since we used intact rats in this experiment, it is possible that increased sex steroid hormone concentrations, especially oestrogen, induced by increased serum LH levels, sensitized the pituitary gland to succeeding LH-RH doses. This possibility, however, seems unlikely because our results were in general agreement with in-vitro results obtained using a pituitary perifusion technique by Waring & Turgeon (1980), and oestrogen is known to inhibit LH responsiveness at the pituitary gland to LH-RH a few hours after injection (Libertun et al 1974;Higuchi & Kawakami, 1982). Response of LH to repeated injections of LH releasing hormone (LH-RH; 300ng/kg body wt; shown by arrows) at 30-min intervals in rats ovariectomized for 120 days.…”
Section: Discussionsupporting
confidence: 88%
“…It is generally accepted that oestrogen is the main factor which modulates pituitary responsiveness to LH-RH. Oestrogen acts directly on the pituitary gland to inhibit or facilitate the LH response to LH-RH, depending on the duration of oestrogen action on the pituitary gland (Libertun, Orias & McCann, 1974;Higuchi & Kawakami, 1982). In the rat, the LH response to LH-RH is highest at pro-oestrus (Cooper, Fawcett & McCann, 1973;Pickering & Fink, 1979), mainly due to the increased levels of circulating oestrogen at late dioestrus and early pro-oestrus (Aiyer & Fink, 1974;Butcher, Collins & Fugo, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with a long-lasting oestrogen, oestradiol benzoate (Table 3) or s.c. implantation of oestradiol-17ß (Weick, 1977) in ovariectomized rats inhibited the LH pulsatile rhythm. In addition, chronic inhibitory effects of oestrogen on LH secretion seems to be induced by inhibiting hypothalamic LH-RH release rather than by inhibiting pituitary responsiveness to LH-RH (Aiyer, Sood & Brown-Grant, 1976;Higuchi & Kawakami, 1982). Thus, oestrogen might be responsible for maintaining the pulse frequency at a low level in cyclic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report (Higuchi & Kawakami, 1982) indicated that the acute inhibitory effect of oestrogen on LH release could be explained by an acute suppressive action of oestrogen on pituitary responsiveness to LH-RH, because a directly inhibitory effect of oestrogen on the pituitary gland could operate in ovariectomized rats with little endogen¬ ous LH-RH after anterior neural deafferentation. An increase of pituitary responsiveness to LH-RH rather than an increase in LH-RH at each pulsatile discharge may play the major role in this enhancement of LH pulse amplitude after ovariectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other investigators have re ported that systemically applied estrogen decreased serum LH levels and/or LH pulse amplitudes but failed to pro duce a modification of the pulse frequency in ovariectom ized rats [12,21,22] and sheep [10], The reason for this discrepancy is not clear. However, it must be taken into ac count that estrogen can act at the level of the pituitary to suppress LH release [11,17]. Inhibition of the pituitary LH output by estrogen would make it difficult to examine the steroid effect on the hypothalamic pulse generator unless pulsatile patterns of LHRH, rather than LH, were mea sured in a physiological condition.…”
Section: Discussionmentioning
confidence: 99%